Vanadium-based catalyst-containing hydrogen storage alloy, and preparation method and application thereof

CN122855972APending Publication Date: 2026-10-02HUANENG CLEAN ENERGY RES INST +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611148421.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-06-29
Filing Date
2026-07-30
Publication Date
2026-10-02

AI Technical Summary

Technical Problem

[0004]本申请针对现有的镁基固态储氢材料热力学稳定性导致其有效脱氢温度较高,限制了其在常温或近常温环境下的实际应用的技术问题,提供一种含钒基催化剂的储氢合金及其制备方法和应用,本申请提供的含钒基催化剂的储氢合金具有较高的储氢动力学和热力学性能

Benefits of technology

本申请提供的含钒基催化剂的储氢合金,在MgH2基体中均匀分散质量分数为5%~15%的V-Ti-Fe系高钒固溶体合金作为催化相。所提供的钒基催化剂本身具备优良的吸放氢动力学特性,能够在温和的温度和压力条件下实现氢的吸放。在复合体系中,钒基催化剂可作为氢原子扩散的快速通道,显著降低MgH2的吸放氢活化能,进而降低材料整体的吸放氢工作温度;同时钒元素会在合金表面及晶界处形成大量活性位点,有效促进氢气分子的解离与复合过程,大幅缩短吸放氢反应的时间。此外,钒的引入能够细化合金晶粒,增加晶界密度,为氢原子的扩散提供更多路径。同时,钒基催化剂中的组成元素与镁基体互不固溶,不会形成新的金属间化合物,能够在多次吸放氢循环过程中保持稳定的催化活性,使镁基储氢材料在较低的操作温度下仍能维持较高的吸放氢动力学性能和储氢容量。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a hydrogen storage alloy containing a vanadium-based catalyst and a preparation method and application thereof. The hydrogen storage alloy is prepared by hydrogenating magnesium to obtain MgH2 nanoparticles, and then performing ball milling and composite treatment on the MgH2 nanoparticles and a vanadium-based catalyst to obtain the hydrogen storage alloy, wherein the hydrogen storage alloy comprises a MgH2 base and a vanadium-based catalyst dispersed in the MgH2 base; the mass fraction of the vanadium-based catalyst is 5% to 15%; and the vanadium-based catalyst is a V-Ti-Fe high-vanadium solid solution alloy. According to mass percentage, the V-Ti-Fe high-vanadium solid solution alloy contains 80% to 90% of V, 5% to 15% of Ti and 5% to 15% of Fe. The prepared hydrogen storage alloy containing the vanadium-based catalyst has excellent hydrogen absorption and release performance, a low working temperature and good cycle stability, and is applied to a solid-state hydrogen storage device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of solid-state hydrogen storage materials technology, specifically relating to a hydrogen storage alloy containing a vanadium-based catalyst, its preparation method, and its application. Background Technology

[0002] Solid-state hydrogen storage is one of the core technologies for the large-scale application of hydrogen energy. Magnesium-based hydrogen storage alloys have become commercially viable solid-state hydrogen storage materials due to their advantages of ultra-high theoretical hydrogen storage capacity of 7.60 wt%, abundant raw materials, and low cost. Vanadium-based solid solution hydrogen storage alloys, on the other hand, have unique characteristics such as room temperature hydrogen absorption and desorption, excellent kinetic performance, and mild working pressure, and have broad application prospects.

[0003] To improve the performance of magnesium-based hydrogen storage alloys, existing technologies mainly focus on introducing various catalysts to accelerate the hydrogen absorption and desorption reaction rates, thus improving kinetic performance to some extent. Meanwhile, significant progress has been made in the research of vanadium-based hydrogen storage alloys. By doping with elements such as cobalt and iron to regulate the alloy composition, optimized systems such as V-Ti-Fe and V-Co have been prepared, further enhancing their hydrogen storage capacity, desorption plateau pressure, and hydrogen absorption and desorption rates, confirming the effective regulatory effect of elemental doping on the performance of vanadium-based alloys. However, existing catalysts for magnesium-based hydrogen storage alloys can only improve kinetic performance and cannot fundamentally reduce the thermodynamic decomposition temperature of MgH2. Even after modification, a temperature above 250℃ is still required to achieve a considerable hydrogen desorption rate, and the thermodynamic bottleneck remains unresolved. On the other hand, although vanadium-based hydrogen storage alloys possess excellent room-temperature kinetic characteristics and suitable operating pressures, their research has been limited to optimizing their performance as independent hydrogen storage materials, while the introduction of them as catalysts into magnesium-based hydrogen storage systems has not yet been explored. Therefore, this application proposes a technical solution to introduce modified vanadium-based alloys as catalysts into magnesium-based hydrogen storage systems, so as to achieve synergistic optimization of the dehydrogenation temperature and hydrogen absorption / desorption rate of magnesium-based hydrogen storage alloys. Summary of the Invention

[0004] This application addresses the technical problem that the thermodynamic stability of existing magnesium-based solid hydrogen storage materials results in a high effective dehydrogenation temperature, which limits their practical application in ambient or near-ambient temperature environments. It provides a hydrogen storage alloy with a vanadium-based catalyst, its preparation method, and its application. The hydrogen storage alloy with a vanadium-based catalyst provided in this application has high hydrogen storage kinetics and thermodynamic performance.

[0005] To achieve the above objectives, this application adopts the following technical solution: The first aspect of this application provides a hydrogen storage alloy containing a vanadium-based catalyst, comprising a MgH2 matrix and a vanadium-based catalyst dispersed in the MgH2 matrix; wherein the mass fraction of the vanadium-based catalyst is 5% to 15%. The vanadium-based catalyst is a V-Ti-Fe system high vanadium solid solution alloy.

[0006] Furthermore, by mass percentage, the V-Ti-Fe series high vanadium solid solution alloy contains 80%~90% V, 5%~15% Ti, and 5%~15% Fe.

[0007] A second aspect of this application provides a method for preparing a hydrogen storage alloy containing a vanadium-based catalyst as described above, comprising the following steps: MgH2 nanoparticles were obtained by hydrogenation of metallic magnesium. The hydrogen storage alloy was obtained by ball milling composite treatment using MgH2 nanoparticles and vanadium-based catalyst.

[0008] Furthermore, the hydrogenation treatment of metallic magnesium specifically involves: subjecting metallic magnesium to a hydrogen plasma metal reaction to obtain Mg nanoparticles, and then hydrogenating the Mg nanoparticles under a hydrogen atmosphere to obtain MgH2 nanoparticles.

[0009] Furthermore, the hydrogen plasma metal reaction is carried out in a mixed atmosphere consisting of 0.08~0.15 bar H2 and 0.6~0.8 bar Ar, and the arc discharge current is 30~80A.

[0010] Furthermore, the hydrogenation treatment temperature is 300~500 ℃, and the hydrogen pressure is 2~10 MPa.

[0011] Furthermore, the vanadium-based catalyst is in powder form, and the particle size of the vanadium-based catalyst is less than 50 μm.

[0012] Furthermore, the vanadium-based catalyst is prepared as a powdered vanadium-based catalyst by gas atomization or electric arc melting combined with hydrogenation crushing.

[0013] Furthermore, the ball-to-material ratio of the ball milling composite treatment is (5~50):1, the rotation speed is 100~800rpm, the ball milling time is 2~6h, and 0.2~5MPa hydrogen gas is introduced during the ball milling process.

[0014] A third aspect of this application provides an application of the hydrogen storage alloy of the vanadium-based catalyst as described above, wherein the hydrogen storage alloy of the vanadium-based catalyst is applied to a solid-state hydrogen storage device.

[0015] Compared with the prior art, this application has the following beneficial effects: The hydrogen storage alloy containing a vanadium-based catalyst provided in this application uses a V-Ti-Fe high-vanadium solid solution alloy with a mass fraction of 5%~15% uniformly dispersed in a MgH2 matrix as the catalytic phase. The provided vanadium-based catalyst itself possesses excellent hydrogen absorption and desorption kinetics, enabling hydrogen absorption and desorption under mild temperature and pressure conditions. In the composite system, the vanadium-based catalyst acts as a rapid channel for hydrogen atom diffusion, significantly reducing the activation energy of hydrogen absorption and desorption in MgH2, thereby lowering the overall hydrogen absorption and desorption operating temperature of the material. Simultaneously, vanadium forms numerous active sites on the alloy surface and at grain boundaries, effectively promoting the dissociation and recombination of hydrogen molecules and significantly shortening the hydrogen absorption and desorption reaction time. Furthermore, the introduction of vanadium refines the alloy grains, increases grain boundary density, and provides more pathways for hydrogen atom diffusion. At the same time, the constituent elements in the vanadium-based catalyst are immiscible with the magnesium matrix, preventing the formation of new intermetallic compounds, and maintaining stable catalytic activity during multiple hydrogen absorption and desorption cycles. This allows the magnesium-based hydrogen storage material to maintain high hydrogen absorption and desorption kinetics and hydrogen storage capacity even at relatively low operating temperatures.

[0016] The proposed method for preparing vanadium-based catalyst hydrogen storage alloys utilizes a proprietary process route designed specifically for the characteristics of the aforementioned composite system. This method first prepares MgH2 particles through a hydrogen plasma-metal reaction combined with subsequent hydrogenation treatment, resulting in a matrix material with uniform particle size. Then, a vanadium-based catalyst is prepared using vacuum melting combined with gas atomization powdering technology, yielding a catalyst powder with uniform composition, high purity, and stable catalytic activity. Finally, a ball milling process is used to achieve uniform composite formation of the catalyst and the MgH2 matrix. The parameters of the entire preparation process are clearly defined and controllable, and the process conditions at each stage have been specifically optimized to ensure the performance of the final product.

[0017] This application applies the aforementioned vanadium-based catalyst hydrogen storage alloy, which possesses excellent hydrogen absorption and desorption performance, low operating temperature, and good cycle stability, to solid-state hydrogen storage devices. Utilizing the alloy's advantage of rapid hydrogen absorption and desorption under mild conditions, the problems of slow hydrogen charging and discharging rates and harsh operating conditions in existing solid-state hydrogen storage devices can be effectively improved, thereby enhancing the practicality of solid-state hydrogen storage systems. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application are described clearly and completely below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0019] With the rapid development of the hydrogen energy industry, solid-state hydrogen storage has become an important development direction for hydrogen storage and transportation technology due to its high safety and high hydrogen storage density. Magnesium-based hydrogen storage alloys are considered one of the most promising solid-state hydrogen storage materials due to their advantages such as high theoretical hydrogen storage capacity, abundant resources, and low cost. However, pure magnesium-based hydrogen storage alloys suffer from defects such as poor hydrogen absorption and desorption kinetics, high reaction activation energy, and high operating temperature, which seriously restrict their practical application. Existing technologies usually improve the performance of magnesium-based hydrogen storage alloys by adding transition metal catalysts, but traditional catalysts have problems such as poor dispersibility, weak bonding with the matrix, and easy agglomeration and deactivation during cycling. Vanadium-based materials have become ideal catalysts for magnesium-based hydrogen storage alloys due to their excellent hydrogen diffusion ability and catalytic activity. However, current methods for preparing vanadium-based catalysts generally suffer from problems such as large powder particle size, low purity, and poor sphericity, resulting in insufficient catalytic effect.

[0020] Based on this, this application provides a hydrogen storage alloy containing a vanadium-based catalyst, comprising a MgH2 matrix and a vanadium-based catalyst uniformly dispersed in the MgH2 matrix. The mass fraction of the vanadium-based catalyst is 5% to 15%, which ensures sufficient catalytic active sites without reducing the overall hydrogen storage capacity of the alloy due to excessive catalyst content.

[0021] The vanadium-based catalyst is a V-Ti-Fe high-vanadium solid solution alloy, with V comprising 80%–90%, Ti 5%–15%, and Fe 5%–15% by mass percentage. This high-vanadium solid solution alloy has a body-centered cubic crystal structure, where the diffusion rate of hydrogen atoms is much higher than in the magnesium matrix, serving as a rapid diffusion channel for hydrogen atoms and significantly reducing the activation energy of hydrogen absorption and desorption in MgH₂. Simultaneously, the addition of Ti and Fe further refines the catalyst grains, increases the number of active sites, and improves catalytic performance. The vanadium-based catalyst is immiscible with the magnesium matrix and does not form intermetallic compounds, ensuring the structural stability and long-lasting catalytic activity of the catalyst during multiple hydrogen absorption and desorption cycles.

[0022] This application also provides a method for preparing the hydrogen storage alloy containing the above-mentioned vanadium-based catalyst, comprising the following steps: MgH2 nanoparticles were obtained by hydrogenation of metallic magnesium. The hydrogen storage alloy was obtained by ball milling composite treatment using MgH2 nanoparticles and vanadium-based catalyst.

[0023] In some specific embodiments of this application, magnesium metal is hydrogenated to obtain MgH2 nanoparticles. Specifically, a hydrogen plasma metal reaction method combined with subsequent hydrogenation is used to prepare MgH2 nanoparticles with fine particle size and high activity, as detailed below: First, Mg nanoparticles were prepared by hydrogen plasma metal reaction: Magnesium ingots, after being sanded to remove oxide scale, were placed in the reaction chamber. The reaction system was sequentially evacuated, helium leak-checked, and argon purged three times to ensure no residual air or moisture remained in the system. A mixed atmosphere of 0.08–0.15 bar H₂ and 0.6–0.8 bar Ar was introduced into the reaction chamber, and the arc discharge device was activated, maintaining a discharge current of 30–80 A after arc ignition. During the reaction, the arc position was dynamically adjusted to uniformly scan the surface of the magnesium ingot, ensuring uniform melting and evaporation. The reaction lasted for 45 minutes, during which a circulation pump was activated to transport and collect the generated Mg nanoparticles in a collection sleeve inside a glove box. After the reaction, under a high-purity argon atmosphere, the Mg nanoparticles in the sleeve were transferred to a sealed sample vial for later use.

[0024] Subsequently, hydrogenation treatment was performed: a certain mass of Mg nanoparticles was accurately weighed and loaded into the sample tube of the Sievert-type hydrogen storage performance testing device. The sample tube was then evacuated to 1×10⁻⁶. -3 The sample was heated to 300-500℃ with a pressure of 2-10 MPa of high-purity hydrogen gas and subjected to constant-temperature hydrogenation for 6 hours to completely convert Mg nanoparticles into MgH2 nanoparticles. After hydrogenation, the sample was allowed to cool naturally to room temperature, unreacted hydrogen gas was removed, and the sample was taken out under argon protection to obtain MgH2 nanoparticles.

[0025] In some specific embodiments of this application, the vanadium-based catalyst is prepared as a powdered vanadium-based catalyst by gas atomization or electric arc melting combined with hydrogenation crushing. The powdered vanadium-based catalyst is then subjected to vibratory sieving and airflow classification under a high-purity argon atmosphere. First, the powder is separated into three particle size ranges: >150 μm, 100~150 μm, and <100 μm by a vibratory sieve, discarding coarse powder larger than 150 μm. The powder smaller than 100 μm is then airflow classified to obtain powders with particle size ranges of <50 μm and 50~100 μm. This application preferably uses ultrafine spherical powder with a particle size of less than 50 μm as the vanadium-based catalyst. The classified powder is sealed and stored in an argon-filled glove box to prevent oxidation.

[0026] In some specific embodiments of this application, the hydrogen storage alloy is obtained by ball milling composite treatment of MgH2 nanoparticles and vanadium-based catalyst, specifically as follows: In a glove box under a high-purity argon atmosphere, MgH2 nanoparticles and vanadium-based catalyst are accurately weighed at a mass fraction of 5%–15%. The weighed vanadium-based catalyst and MgH2 nanoparticles are transferred to a ball mill jar, with a ball-to-material ratio controlled at (5–50):1. After sealing the ball mill jar, the glove box is removed, a gas pipeline is connected, and after evacuation, high-purity hydrogen gas at 0.2–5 MPa is introduced into the jar as a protective atmosphere and hydrogen source during the ball milling process. The ball milling speed is set to 100–800 rpm, and the ball milling time is 2–6 hours. After ball milling, the ball mill jar is allowed to cool naturally to room temperature. The hydrogen gas inside the jar is slowly released, and then the ball mill jar is transferred to the glove box, the lid is opened, and the ball milling product is taken out, which is the hydrogen storage alloy containing the vanadium-based catalyst. The obtained product is sealed and stored in a glove box filled with high-purity argon gas and equipped with a desiccant to prevent oxidation and moisture absorption.

[0027] The hydrogen storage alloy containing vanadium-based catalysts prepared in this application can be widely used in solid-state hydrogen storage devices.

[0028] The present application will be further described in detail below with reference to specific embodiments. The specific embodiments described below are only used to further illustrate the present application and are not intended to limit the scope of protection of the present application.

[0029] Unless otherwise defined, all terms used below shall be interpreted in accordance with their meaning as commonly understood by those skilled in the art. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in this application may be obtained commercially or prepared by existing methods.

[0030] Example 1 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 5%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 85%, Ti 10%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Magnesium ingots, after being polished to remove oxide scale, were placed in a reaction chamber. Vacuuming, leak detection, and three argon gas purging operations were performed sequentially. A mixed atmosphere of 0.1 bar H2 and 0.7 bar Ar was introduced, and an electric arc discharge was initiated and maintained at a current of 60 A. The arc position was dynamically adjusted to uniformly scan the surface of the magnesium ingot. After reacting for 45 min, the generated Mg nanoparticles were collected. The Mg nanoparticles were loaded into a sample tube of a Sievert-type apparatus and hydrogenated at a constant temperature of 400℃ and 4 MPa high-purity hydrogen for 6 h to obtain MgH2 nanoparticles.

[0031] Preparation of vanadium-based catalyst: Weigh metallic vanadium, titanium, and iron raw materials with a purity ≥99.9% according to the above component ratios, and load them into a vacuum magnetic levitation melting furnace. Evacuate to 5×10⁻⁶. -3After the pressure was below 100 Pa, 0.05 MPa of high-purity argon gas was introduced for protection. The melting power was set to 200 kW, and the temperature was raised until the alloy was completely melted. The temperature was then held for 60 min, and the crucible was repeatedly turned over 4 times to promote uniform composition. The molten alloy was poured into a preheated cylindrical mold at 200 °C. After cooling and demolding, it was machined into electrode rods. Powder was prepared using the electrode induction melting gas atomization method, with the melting power set at 35 kW, atomization pressure at 6 MPa, electrode feed speed at 60 mm / min, and rotation speed at 150 RPM. The powder was then obtained by vibration sieving and airflow classification to obtain vanadium-based catalysts with a particle size of less than 50 μm.

[0032] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.475g of MgH2 nanoparticles and 0.025g of vanadium-based catalyst, totaling 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, evacuate and purge with 2MPa high-purity hydrogen. Set the milling speed to 400rpm and the milling time to 4h, using an alternating forward and reverse rotation mode, pausing for 10min every 30min of operation. After milling, cool to room temperature, slowly release the hydrogen from the jar, remove the product from the glove box, and seal it for storage in an argon-filled environment.

[0033] Example 2 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 85%, Ti 10%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Same as in Example 1.

[0034] Preparation of vanadium-based catalyst: Same as in Example 1.

[0035] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst, for a total mass of 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, evacuate and purge with 2MPa high-purity hydrogen. Set the milling speed to 400rpm and the milling time to 4h, using an alternating forward and reverse rotation mode, pausing for 10min every 30min of operation. After milling, cool to room temperature, slowly release the hydrogen from the jar, remove the product from the glove box, and seal it for storage in an argon-filled environment.

[0036] Example 3 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 15%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 85%, Ti 10%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Same as in Example 1.

[0037] Preparation of vanadium-based catalyst: Same as in Example 1.

[0038] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.425g of MgH2 nanoparticles and 0.075g of vanadium-based catalyst, totaling 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, evacuate and purge with 2MPa of high-purity hydrogen. Install in a planetary ball mill, set the speed to 400rpm, and the milling time to 4h, using an alternating forward and reverse rotation mode, pausing for 10min every 30min of operation. After ball milling, cool to room temperature, slowly release the hydrogen from the jar, remove the product from the glove box, and seal it for storage in an argon-filled environment.

[0039] The hydrogen storage performance of the hydrogen storage alloys with vanadium-based catalysts prepared in Examples 1-3 was tested. The results showed that the sample with 10 wt% catalyst added had the fastest hydrogen release rate, reaching 6.8 wt% at 250 °C; the sample with 15 wt% catalyst added had a relatively fast hydrogen release rate, but its hydrogen storage capacity decreased to 6.2 wt%; the sample with 5 wt% catalyst added still had a hydrogen release temperature above 300 °C. This indicates that 10 wt% is the optimal addition amount.

[0040] Example 4 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 80%, Ti 15%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Magnesium ingots, after being polished to remove oxide scale, were placed in a reaction chamber. Vacuuming, leak detection, and three argon gas purging operations were performed sequentially. A mixed atmosphere of 0.1 bar H2 and 0.7 bar Ar was introduced, and an electric arc discharge was initiated and maintained at a current of 60 A. The arc position was dynamically adjusted to uniformly scan the surface of the magnesium ingot. After reacting for 45 min, the generated Mg nanoparticles were collected. The Mg nanoparticles were loaded into a sample tube of a Sievert-type apparatus and hydrogenated at a constant temperature of 400℃ and 4 MPa high-purity hydrogen for 6 h to obtain MgH2 nanoparticles.

[0041] Preparation of vanadium-based catalyst: Weigh metallic vanadium, titanium, and iron raw materials with a purity ≥99.9% according to the above component ratios, and load them into a vacuum magnetic levitation melting furnace. Evacuate to 5×10⁻⁶. -3After the pressure was below 100 Pa, 0.05 MPa of high-purity argon gas was introduced for protection. The melting power was set to 200 kW, and the temperature was raised until the alloy was completely melted. The temperature was then held for 60 min, and the crucible was repeatedly turned over 4 times to promote uniform composition. The molten alloy was poured into a preheated cylindrical mold at 200 °C. After cooling and demolding, it was machined into electrode rods. Powder was prepared using the electrode induction melting gas atomization method with a melting power of 35 kW, an atomization pressure of 6 MPa, an electrode feed speed of 60 mm / min, and a rotation speed of 150 RPM. The powder was then obtained by vibration sieving and airflow classification to obtain vanadium-based catalysts with a particle size of less than 50 μm.

[0042] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst, totaling 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, evacuate and purge with 2MPa of high-purity hydrogen. Install in a planetary ball mill, set the speed to 400rpm, and mill for 2 hours, using an alternating forward and reverse rotation mode, pausing for 10 minutes every 30 minutes of operation. After ball milling, cool to room temperature, slowly release the hydrogen from the jar, remove the product from the glove box, and seal it for storage in an argon-filled environment.

[0043] Example 5 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 80%, Ti 15%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Same as in Example 4.

[0044] Preparation of vanadium-based catalyst: Same as in Example 4.

[0045] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst, for a total mass of 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, evacuate and purge with 2MPa high-purity hydrogen. Set the milling speed to 400rpm and the milling time to 4h, using an alternating forward and reverse rotation mode, pausing for 10min every 30min of operation. After milling, cool to room temperature, slowly release the hydrogen from the jar, remove the product from the glove box, and seal it for storage in an argon-filled environment.

[0046] Example 6 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 80%, Ti 15%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Same as in Example 4.

[0047] Preparation of vanadium-based catalyst: Same as in Example 4.

[0048] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst, totaling 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, evacuate and purge with 2MPa of high-purity hydrogen. Install in a planetary ball mill, set the speed to 400rpm, and the milling time to 6h, using an alternating forward and reverse rotation mode, pausing for 10min every 30min of operation. After milling, cool to room temperature, slowly release the hydrogen from the jar, remove the product from the glove box, and seal it for storage in an argon-filled environment.

[0049] The hydrogen storage performance of the vanadium-based catalysts prepared in Examples 4-6 was tested. The results showed that the sample ball-milled for 4 hours had the highest hydrogen release (6.7 wt%) at 250°C and the best hydrogen absorption and desorption rates. The sample ball-milled for 2 hours had uneven catalyst distribution, and the hydrogen release temperature was still above 280°C. The sample ball-milled for 6 hours showed partial amorphization, and the hydrogen storage capacity decreased to 6.3 wt%. This indicates that moderate ball milling helps to uniformly disperse the catalyst, but excessive ball milling may lead to structural damage.

[0050] Example 7 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 90%, Ti 5%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Magnesium ingots, after being polished to remove oxide scale, were placed in a reaction chamber. Vacuuming, leak detection, and three argon gas purging operations were performed sequentially. A mixed atmosphere of 0.1 bar H2 and 0.7 bar Ar was introduced, and an electric arc discharge was initiated and maintained at a current of 60 A. The arc position was dynamically adjusted to uniformly scan the surface of the magnesium ingot. After reacting for 45 min, the generated Mg nanoparticles were collected. The Mg nanoparticles were loaded into a sample tube of a Sievert-type apparatus and hydrogenated at a constant temperature of 400℃ and 4 MPa high-purity hydrogen for 6 h to obtain MgH2 nanoparticles.

[0051] Preparation of vanadium-based catalyst: Weigh metallic vanadium, titanium, and iron raw materials with a purity ≥99.9% according to the above component ratios, and load them into a vacuum magnetic levitation melting furnace. Evacuate to 5×10⁻⁶. -3After the pressure was below 100 Pa, 0.05 MPa of high-purity argon gas was introduced for protection. The melting power was set to 200 kW, and the temperature was raised until the alloy was completely melted. The temperature was then held for 60 min, and the crucible was repeatedly turned over 4 times to promote uniform composition. The molten alloy was poured into a preheated cylindrical mold at 200 °C. After cooling and demolding, it was machined into electrode rods. Powder was prepared using the electrode induction melting gas atomization method with a melting power of 35 kW, an atomization pressure of 6 MPa, an electrode feed speed of 60 mm / min, and a rotation speed of 150 RPM. The powder was then obtained by vibration sieving and airflow classification to obtain vanadium-based catalysts with a particle size of less than 50 μm.

[0052] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst, totaling 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, evacuate and purge with 2MPa of high-purity hydrogen. Install in a planetary ball mill, set the speed to 400rpm, and the milling time to 4h, using an alternating forward and reverse rotation mode, pausing for 10min every 30min of operation. After ball milling, cool to room temperature, slowly release the hydrogen from the jar, remove the product from the glove box, and seal it for storage in an argon-filled environment.

[0053] Example 8 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 85%, Ti 10%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Same as in Example 7.

[0054] Preparation of vanadium-based catalyst: Weigh metallic vanadium, titanium, and iron raw materials with a purity ≥99.9% according to the above component ratios, and load them into a vacuum magnetic levitation melting furnace. Evacuate to 5×10⁻⁶. -3 After the pressure was below 100 Pa, 0.05 MPa of high-purity argon gas was introduced for protection. The melting power was set to 200 kW, and the temperature was raised until the alloy was completely melted. The temperature was then held for 60 min, and the crucible was repeatedly turned over 4 times to promote uniform composition. The molten alloy was poured into a preheated cylindrical mold at 200 °C. After cooling and demolding, it was machined into electrode rods. Powder was prepared using the electrode induction melting gas atomization method with a melting power of 35 kW, an atomization pressure of 6 MPa, an electrode feed speed of 60 mm / min, and a rotation speed of 150 RPM. The powder was then obtained by vibration sieving and airflow classification to obtain vanadium-based catalysts with a particle size of less than 50 μm.

[0055] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst, totaling 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, evacuate and purge with 2MPa of high-purity hydrogen. Install in a planetary ball mill, set the speed to 400rpm, and the milling time to 4h, using an alternating forward and reverse rotation mode, pausing for 10min every 30min of operation. After ball milling, cool to room temperature, slowly release the hydrogen from the jar, remove the product from the glove box, and seal it for storage in an argon-filled environment.

[0056] Example 9 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 80%, Ti 15%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Same as in Example 7.

[0057] Preparation of vanadium-based catalyst: Weigh metallic vanadium, titanium, and iron raw materials with a purity ≥99.9% according to the above component ratios, and load them into a vacuum magnetic levitation melting furnace. Evacuate to 5×10⁻⁶. -3 After the pressure was below 100 Pa, 0.05 MPa of high-purity argon gas was introduced for protection. The melting power was set to 200 kW, and the temperature was raised until the alloy was completely melted. The temperature was then held for 60 min, and the crucible was repeatedly turned over 4 times to promote uniform composition. The molten alloy was poured into a preheated cylindrical mold at 200 °C. After cooling and demolding, it was machined into electrode rods. Powder was prepared using the electrode induction melting gas atomization method with a melting power of 35 kW, an atomization pressure of 6 MPa, an electrode feed speed of 60 mm / min, and a rotation speed of 150 RPM. The powder was then obtained by vibration sieving and airflow classification to obtain vanadium-based catalysts with a particle size of less than 50 μm.

[0058] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst, totaling 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, evacuate and purge with 2MPa of high-purity hydrogen. Install in a planetary ball mill, set the speed to 400rpm, and the milling time to 4h, using an alternating forward and reverse rotation mode, pausing for 10min every 30min of operation. After ball milling, cool to room temperature, slowly release the hydrogen from the jar, remove the product from the glove box, and seal it for storage in an argon-filled environment.

[0059] The hydrogen storage performance of the hydrogen storage alloys with vanadium-based catalysts prepared in Examples 7-9 was tested. The test results showed that: V 85 Ti 10 Fe5 showed the best catalytic effect, with a hydrogen release of 6.8 wt% at 250℃ and a hydrogen release plateau pressure of 0.15 MPa; V85 Ti 10 The Fe5 hydrogen release plateau pressure is slightly higher, but the hydrogen release rate is slightly lower (6.5 wt%); V 90 The hydrogen release temperature of Ti5Fe5 is still above 280℃, indicating that the introduction of appropriate amounts of Ti and Fe is beneficial to improving thermodynamic properties.

[0060] Example 10 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 85%, Ti 10%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Magnesium ingots, after being polished to remove oxide scale, were placed in a reaction chamber. Vacuuming, leak detection, and three argon gas purging operations were performed sequentially. A mixed atmosphere of 0.1 bar H2 and 0.7 bar Ar was introduced, and an electric arc discharge was initiated and maintained at a current of 60 A. The arc position was dynamically adjusted to uniformly scan the surface of the magnesium ingot. After reacting for 45 min, the generated Mg nanoparticles were collected. The Mg nanoparticles were loaded into a sample tube of a Sievert-type apparatus and hydrogenated at a constant temperature of 400℃ and 4 MPa high-purity hydrogen for 6 h to obtain MgH2 nanoparticles.

[0061] Preparation of vanadium-based catalyst: Weigh metallic vanadium, titanium, and iron raw materials with a purity ≥99.9% according to the above component ratios, and load them into a vacuum magnetic levitation melting furnace. Evacuate to 5×10⁻⁶. -3 After the pressure was below 100 Pa, 0.05 MPa of high-purity argon gas was introduced for protection. The melting power was set to 200 kW, and the temperature was raised until the alloy was completely melted. The temperature was then held for 60 min, and the crucible was repeatedly turned over 4 times to promote uniform composition. The molten alloy was poured into a preheated cylindrical mold at 200 °C. After cooling and demolding, it was machined into electrode rods. Powder was prepared using the electrode induction melting gas atomization method with a melting power of 35 kW, an atomization pressure of 6 MPa, an electrode feed speed of 60 mm / min, and a rotation speed of 150 RPM. The powder was then obtained by vibration sieving and airflow classification to obtain vanadium-based catalysts with a particle size of less than 50 μm.

[0062] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst, totaling 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, remove the glove box and evacuate to 1×10⁻⁶. -2 Below 100 Pa, add 2 MPa of high-purity hydrogen. Install it in a planetary ball mill, set the speed to 400 rpm, and the milling time to 4 hours, using an alternating forward and reverse rotation mode, pausing for 10 minutes every 30 minutes of operation. After milling, cool to room temperature, slowly release the hydrogen from the jar, transfer the milling jar to a glove box, open the lid to remove the product, and seal it for storage in an argon-filled environment.

[0063] Comparative Example 1 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this comparative example, the vanadium-based catalyst had a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used was (mass percentage): V 85%, Ti 10%, Fe 5%. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Same as in Example 10.

[0064] Preparation of vanadium-based catalyst: Same as in Example 10.

[0065] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst, totaling 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, remove the glove box and evacuate to 1×10⁻⁶. -2 Below 100 Pa, purge with 2 MPa of high-purity argon. Install in a planetary ball mill, set the speed to 400 rpm, and the milling time to 4 hours, using an alternating forward and reverse rotation mode, pausing for 10 minutes every 30 minutes of operation. After milling, cool to room temperature, slowly release the argon gas from the jar, transfer the milling jar to a glove box, open the lid, remove the product, and seal it for storage in an argon-filled environment.

[0066] Hydrogen storage performance tests were conducted on the vanadium-based catalyst-containing hydrogen storage alloys prepared in Example 10 and Comparative Example 1. The test results showed that the material ball-milled under H2 atmosphere had the highest hydrogen release capacity (6.8 wt%) at 250°C and the fastest hydrogen absorption and desorption rates. Under the same pressure, the hydrogen release temperature of the ball-milled sample increased to above 280°C under Ar atmosphere, and the hydrogen storage capacity decreased to 6.1 wt%. This indicates that H2 atmosphere is conducive to hydride formation and uniform catalyst dispersion.

[0067] Example 11 In the hydrogen storage alloy containing vanadium-based catalyst prepared in this embodiment, the vanadium-based catalyst has a mass fraction of 10%, and the composition of the V-Ti-Fe high-vanadium solid solution alloy used is (mass percentage): V 85%, Ti 10%, Fe 5%, and the catalyst particle size is less than 50 μm. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Magnesium ingots, after being polished to remove oxide scale, were placed in a reaction chamber. Vacuuming, leak detection, and three argon gas purging operations were performed sequentially. A mixed atmosphere of 0.1 bar H2 and 0.7 bar Ar was introduced, and an electric arc discharge was initiated and maintained at a current of 60 A. The arc position was dynamically adjusted to uniformly scan the surface of the magnesium ingot. After reacting for 45 min, the generated Mg nanoparticles were collected. The Mg nanoparticles were loaded into a sample tube of a Sievert-type apparatus and hydrogenated at a constant temperature of 400℃ and 4 MPa high-purity hydrogen for 6 h to obtain MgH2 nanoparticles.

[0068] Preparation of vanadium-based catalyst: Weigh metallic vanadium, titanium, and iron raw materials with a purity ≥99.9% according to the above component ratios, and load them into a vacuum magnetic levitation melting furnace. Evacuate to 5×10⁻⁶. -3 After the pressure was below 100 Pa, 0.05 MPa of high-purity argon gas was introduced for protection. The melting power was set to 200 kW, and the temperature was raised until the alloy was completely melted. The temperature was then held for 60 min, and the crucible was repeatedly turned over 4 times to promote uniform composition. The molten alloy was poured into a preheated cylindrical mold at 200 °C. After cooling and demolding, it was machined into electrode rods. Powder was prepared using the electrode induction melting gas atomization method with a melting power of 35 kW, an atomization pressure of 6 MPa, an electrode feed speed of 60 mm / min, and a rotation speed of 150 RPM. The powder was then obtained by vibration sieving and airflow classification to obtain vanadium-based catalysts with a particle size of less than 50 μm.

[0069] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst with the above particle size, for a total mass of 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, remove the glove box and evacuate to 1×10⁻⁶. -2 Below 100 Pa, add 2 MPa of high-purity hydrogen. Install it in a planetary ball mill, set the speed to 400 rpm, and the milling time to 4 hours, using an alternating forward and reverse rotation mode, pausing for 10 minutes every 30 minutes of operation. After milling, cool to room temperature, slowly release the hydrogen from the jar, transfer the milling jar to a glove box, open the lid to remove the product, and seal it for storage in an argon-filled environment.

[0070] Comparative Example 2 In the hydrogen storage alloy containing vanadium-based catalyst prepared in this comparative example, the vanadium-based catalyst had a mass fraction of 10%, and the composition (mass percentage) of the V-Ti-Fe high-vanadium solid solution alloy used was: V 85%, Ti 10%, Fe 5%, with a catalyst particle size of 50~100 μm. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Same as in Example 11.

[0071] Preparation of vanadium-based catalyst: Weigh metallic vanadium, titanium, and iron raw materials with a purity ≥99.9% according to the above component ratios, and load them into a vacuum magnetic levitation melting furnace. Evacuate to 5×10⁻⁶. -3 After the pressure was below 0.05 MPa, high-purity argon gas was introduced for protection. The melting power was set to 200 kW, and the temperature was raised until the alloy was completely melted. The temperature was then held for 60 minutes, and the crucible was repeatedly turned over 4 times to promote uniform composition. The molten alloy was poured into a preheated cylindrical mold at 200 °C. After cooling and demolding, the alloy was machined into electrode rods. Powder was prepared using the electrode induction melting gas atomization method with a melting power of 35 kW, an atomization pressure of 6 MPa, an electrode feed speed of 60 mm / min, and a rotation speed of 150 RPM. The powder was then obtained by vibration sieving and air classification to obtain vanadium-based catalysts with a particle size of 50-100 μm.

[0072] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst with the above particle size, for a total mass of 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, remove the glove box and evacuate to 1×10⁻⁶. -2 Below 100 Pa, add 2 MPa of high-purity hydrogen. Install it in a planetary ball mill, set the speed to 400 rpm, and the milling time to 4 hours, using an alternating forward and reverse rotation mode, pausing for 10 minutes every 30 minutes of operation. After milling, cool to room temperature, slowly release the hydrogen from the jar, transfer the milling jar to a glove box, open the lid to remove the product, and seal it for storage in an argon-filled environment.

[0073] Comparative Example 3 In the hydrogen storage alloy containing a vanadium-based catalyst prepared in this comparative example, the vanadium-based catalyst had a mass fraction of 10%, and the composition (mass percentage) of the V-Ti-Fe high-vanadium solid solution alloy used was: V 85%, Ti 10%, Fe 5%, with a catalyst particle size greater than 100 μm. The specific preparation steps are as follows: Preparation of MgH2 nanoparticles: Same as in Example 11.

[0074] Preparation of vanadium-based catalyst: Weigh metallic vanadium, titanium, and iron raw materials with a purity ≥99.9% according to the above component ratios, and load them into a vacuum magnetic levitation melting furnace. Evacuate to 5×10⁻⁶. -3 After the pressure was below 100 MPa, 0.05 MPa of high-purity argon gas was introduced for protection. The melting power was set to 200 kW, and the temperature was raised until the alloy was completely melted. The temperature was then held for 60 minutes, and the crucible was repeatedly turned over 4 times to promote uniform composition. The molten alloy was poured into a preheated cylindrical mold at 200 °C. After cooling and demolding, the alloy was machined into electrode rods. Powder was prepared using the electrode induction melting gas atomization method with a melting power of 35 kW, an atomization pressure of 6 MPa, an electrode feed speed of 60 mm / min, and a rotation speed of 150 RPM. The powder was then obtained by vibrating sieve separation, resulting in vanadium-based catalysts with a particle size greater than 100 μm.

[0075] Ball milling composite treatment: In a high-purity argon glove box, accurately weigh 0.45g of MgH2 nanoparticles and 0.05g of vanadium-based catalyst with the above particle size, for a total mass of 0.5g. Load the raw materials and stainless steel grinding balls into a ball mill jar at a ball-to-material ratio of 20:1. After sealing, remove the glove box and evacuate to 1×10⁻⁶. -2 Below 100 Pa, add 2 MPa of high-purity hydrogen. Install it in a planetary ball mill, set the speed to 400 rpm, and the milling time to 4 hours, using an alternating forward and reverse rotation mode, pausing for 10 minutes every 30 minutes of operation. After milling, cool to room temperature, slowly release the hydrogen from the jar, transfer the milling jar to a glove box, open the lid to remove the product, and seal it for storage in an argon-filled environment.

[0076] The hydrogen storage performance of the vanadium-based catalysts prepared in Example 11 and Comparative Examples 2 and 3 was tested. The results showed that the catalyst sample with a particle size of <50 μm had the highest hydrogen release (6.9 wt%) and the fastest hydrogen release rate at 250 °C; the hydrogen release of the 50-100 μm sample was 6.5 wt%; and the hydrogen release of the >100 μm sample was only 5.8 wt%, with a hydrogen release temperature higher than 300 °C. This indicates that the smaller the catalyst particle size and the more uniform the dispersion, the more significant the catalytic effect.

[0077] The embodiments described above are merely preferred embodiments of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various improvements and substitutions without departing from the technical principles of this application, and these improvements and substitutions should also be considered within the scope of protection of this application. Therefore, the scope of protection of this patent application should be determined by the scope of the claims.

Claims

1. A hydrogen storage alloy containing a vanadium-based catalyst, characterized in that, It includes a MgH2 matrix and a vanadium-based catalyst dispersed in the MgH2 matrix; the mass fraction of the vanadium-based catalyst is 5%~15%; The vanadium-based catalyst is a V-Ti-Fe system high vanadium solid solution alloy.

2. The hydrogen storage alloy containing a vanadium-based catalyst according to claim 1, characterized in that, By mass percentage, the V-Ti-Fe series high vanadium solid solution alloy contains 80%~90% V, 5%~15% Ti, and 5%~15% Fe.

3. A method for preparing a hydrogen storage alloy with a vanadium-based catalyst according to any one of claims 1 or 2, characterized in that, Includes the following steps: MgH2 nanoparticles were obtained by hydrogenation of metallic magnesium. The hydrogen storage alloy was obtained by ball milling composite treatment using MgH2 nanoparticles and vanadium-based catalyst.

4. The method for preparing the hydrogen storage alloy containing a vanadium-based catalyst according to claim 3, characterized in that, The hydrogenation treatment of magnesium metal specifically involves: subjecting magnesium metal to a hydrogen plasma metal reaction to obtain Mg nanoparticles, and then hydrogenating the Mg nanoparticles under a hydrogen atmosphere to obtain MgH2 nanoparticles.

5. The method for preparing the hydrogen storage alloy containing a vanadium-based catalyst according to claim 4, characterized in that, The hydrogen plasma metal reaction is carried out in a mixed atmosphere of 0.08~0.15 bar H2 and 0.6~0.8 bar Ar, and the arc discharge current is 30~80A.

6. The method for preparing the hydrogen storage alloy containing a vanadium-based catalyst according to claim 3, characterized in that, The hydrogenation treatment is carried out at a temperature of 300~500 ℃ and a hydrogen pressure of 2~10 MPa.

7. The method for preparing the hydrogen storage alloy containing a vanadium-based catalyst according to claim 3, characterized in that, The vanadium-based catalyst is in powder form, and the particle size of the vanadium-based catalyst is less than 50 μm.

8. The method for preparing the hydrogen storage alloy containing a vanadium-based catalyst according to claim 3, characterized in that, The vanadium-based catalyst is prepared as a powder by gas atomization or by electric arc melting combined with hydrogenation crushing.

9. The method for preparing the hydrogen storage alloy containing a vanadium-based catalyst according to claim 3, characterized in that, The ball-to-material ratio for the ball milling composite treatment is (5~50):1, the rotation speed is 100~800rpm, the ball milling time is 2~6h, and 0.2~5MPa hydrogen gas is introduced during the ball milling process.

10. The application of a hydrogen storage alloy based on a vanadium-containing catalyst according to any one of claims 1 or 2, characterized in that, The hydrogen storage alloy containing the vanadium-based catalyst is applied to a solid-state hydrogen storage device.